Advances in Stretchable Polymer Semiconductors Design Strategies and Applications in Human-Machine Interaction and Bioelectronics - Wang, Zhihui (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2025 Wiley‐VCH GmbH.